SPE Asia Pacific Oil and Gas Conference and Exhibition 2004
DOI: 10.2118/88591-ms
|View full text |Cite
|
Sign up to set email alerts
|

In-situ In-situ Cross-Linking Acid Diverting Agent (ISCADA): A New Solution to Stimulate Multi-Layered Reservoirs

Abstract: Stimulation of wells completed in multiple layers has always remained a challenge with regards to stimulating all the layers uniformly and effectively. Problems are more severe if the sub-layers of the formation have different petro-physical characteristics and have varying degree of permeability contrast. Stimulation treatments without diversion system applied in these multi-layered wells mainly stimulate the high permeable streaks repeatedly. PH and temperature sensitive In-Situ Cross-linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The apparent viscosity of the in-situ gelled acid is a preferred mechanism in diversion because it creates a viscosity differential in treated and untreated zones. Halder et al (2004) concluded that field application of polymer-based in-situ gelled acids demonstrated an effective diversion in high permeable heterogeneous reservoirs. Based on lab results and field data, these systems can be applied as diversion agents for multi-layered wells in carbonate reservoirs up to 120°C.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent viscosity of the in-situ gelled acid is a preferred mechanism in diversion because it creates a viscosity differential in treated and untreated zones. Halder et al (2004) concluded that field application of polymer-based in-situ gelled acids demonstrated an effective diversion in high permeable heterogeneous reservoirs. Based on lab results and field data, these systems can be applied as diversion agents for multi-layered wells in carbonate reservoirs up to 120°C.…”
Section: Introductionmentioning
confidence: 99%